Dinâmica do componente arbóreo de um fragmento de floresta estacional semidecidual em estado avançado de sucessão - Naves, Emmanuel Rezende (2014)
The increasing land demand for agriculture and urban use contribute for environment degradation. Semi-deciduous seasonal forests (FES), occurring in areas of great population density and relevant economic interest on soil use and occupation remain in marginal areas, especially due to law enforcement (legal reservation and permanent preservation areas). Such lack of care about forest stands and, mostly, about FES explains its fragmented and impoverished florist composition. This study evaluated the conservation status of a forest community, considering the variation in floristic composition, successional group of component species, importance, dominance abundance and frequency of each species; diameter and vertical distribution over a period of five years. The initial hypothesis is that forest fragment isolation would lead to changes in dynamic parameters and in forest composition in time. However, no significant changes were observed in the study area, denoting forest fragment stability. Forest composition did not have marked changes between 2007 and 2012. However, the area presents atypical dominance of some species and such dominance increased during the study period, as shown by the increase in the number of low density occurring species. Forest fragmentation, presently, seems to have had no effect on community dynamic processes. It is unknown if the peculiar species composition and their high dominances in this fragment is the result of fragmentation process, or an interaction between fragmentation and preservation, or if it is a fruit of fragment maturity and preservation. A small decrease in basal area was observed along the five years, resulting from a predominance of mortality over recruitment. However, most species observed basal area increase. The fragment is composed, mostly, by Micrandra elata. This species had such an influence that affected diameter distribution, space distribution, and abundance in the Forest community studied.